2019
DOI: 10.1016/j.jclepro.2019.02.270
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of organic resources by black soldier fly larvae: Legislation, efficiency and environmental impact

Abstract: To meet the projected substantial growth in the global demand for meat, we are challenged to develop additional protein-rich feed ingredients while minimizing the use of natural resources. The larvae of the black soldier fly (BSF) have the capacity to convert low-value organic resources into a high quality protein source for pigs, chickens and fish and as such may increase both the productivity and the efficiency of the food chain. The aim of this study was to assess the environmental opportunities of BSF larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
178
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(183 citation statements)
references
References 44 publications
2
178
1
2
Order By: Relevance
“…Hermetia illucens larvae have been suggested to have an important role to play in the framework of the circular economy by recycling resources that are normally eliminated or that do not find a reallocation in the food chain [18,43,44]. Larvae of this fly can feed on a wide range of organic substrates characterized by a different content of nutrients producing high-rich protein feed for livestock [16,31,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hermetia illucens larvae have been suggested to have an important role to play in the framework of the circular economy by recycling resources that are normally eliminated or that do not find a reallocation in the food chain [18,43,44]. Larvae of this fly can feed on a wide range of organic substrates characterized by a different content of nutrients producing high-rich protein feed for livestock [16,31,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…regulations prohibit the use of insects in the food chain if they are grown on manure or waste of animal origin. Nevertheless, many papers have shown that the environmental impact of insect production is highly influenced by the insect rearing substrate [43,44,47,48]. Thus, the possibility to exploit different waste streams could lower the environmental impact of insect mass production compared to the feed currently used (mainly feed for poultry) as well as contributing to the waste management.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is possible to use organic side streams as feed for the insects. Bosch et al (2019) reviewed forty articles dealing with environmental impact (global warming potential, energy use, and land use) of manure, catering waste or municipal waste conversion by black soldier fly larvae. The impact was lower than that of fishmeal and soy, but not when larvae converted substrates which contained food and feed products such as sorghum and DDGS (dried distillers' grains with solubles).…”
Section: Environmentmentioning
confidence: 99%
“…Insects convert their feed more efficiently than pigs and cattle (Bosch et al, 2019;Dobermann et al, 2017;Halloran et al, 2018;, which contributes to their importance for valorizing organic waste streams (Chia et al, 2018b). Sustainability of insect production is highest if the insects are fed with organic resources that are currently not suitable as feed for livestock.…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
“…Current protein sources in feed are soybean meal and fishmeal whose use is under pressure because of environmental aspects (Dicke, 2018). Therefore, rearing BSF as feed may mitigate environmental impact of feed production (Bosch et al, 2019).…”
Section: Environmental Sustainabilitymentioning
confidence: 99%